Analisis Fasilitas dan Aksesibilitas Halte dan Stasiun Kereta Commuter Surabaya Porong - Soimun, Ahmad; Leliana, Arinda (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
The city of Surabaya is the center of activities such as trade, business industry, and the center of government, so it demands people to visit the city. To attract the interest of the hinterland community, public transportation is needed that can be a mainstay and pay attention to service schedules, punctuality, and headway. So that public transportation can reduce the level of congestion in the destination city, in this case, the city of Surabaya. It is also necessary to think about connectivity, facilities, and accessibility at the bus stop station as a good place for passengers to drop off. The Surabaya Porong commuter train must be connected to other transportation so that it is necessary to pay attention to facilities and accessibility at every bus stop and station. Data collection and surveys are carried out by direct observation in the field with surveys, observing and measuring existing facilities and accessibility. The facilities and accessibility of the Surabaya Porong bus stop and commuter train station appear to have been partially available, although there are shortcomings, they can still run for the operations of the communities around Surabaya and Sidoarjo. Based on the results of the analysis of the pedestrian flow rate at the time of the study, the LOS values ​​for bus stops and stations were still very good with the AB category.